Penerapan Akses Internet Bersama Warga di Lingkungan Perumahan Griya Ciledug - Wiharto, Yudi; Subandi Subandi; Mufti, Mufti; Gata, Grace; Diana, Anita (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This Community Service Activity aims to provide a solution for equitable and affordable internet access for residents in the Griya Ciledug Housing area. In today's era, internet connectivity has become a basic need that not only supports communication activities, but also education, economy, and social services. Through a participatory approach, this activity actively involves residents in the planning, installation, and management of a shared internet network system. The results of the activity show a significant increase in the availability of internet access in the area, strengthening collaboration between residents, and increasing digital literacy. In addition, the active involvement of residents in network management also encourages a sense of ownership and collective responsibility. This activity is a model of technology-based community empowerment that can be replicated in other environments with similar needs.